Da'wah Methods in Qur'anic Invitations to Reflect on the Universe - Fauziah, Mira (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The Qur'an commands Muslims to observe and interpret the universe rationally, considering natural phenomena as signs of Allah's existence and guidance for humankind. This study explores the Qur'anic method of da'wah through verses inviting reflection on the universe. Employing a qualitative research design and a thematic analysis approach, the study examines Qur'anic verses related to natural phenomena and their implications for da'wah. Primary data sources include ayat kawniyyah (verses about natural phenomena) from the Qur'an, with secondary data from classical and contemporary Islamic scholarship, tafsir literature, and scientific studies on environmental preservation. The analysis reveals that the Qur'an emphasizes the observation and study of the universe, highlighting its creation, balance, and order by Allah. The study identifies three main da'wah methods: da’wah bi al-Hāl (concrete actions in environmental conservation), da’wah bi al-lisan (rational and scientific argumentation), and da’wah bi al-qalb (fostering opposition to environmental destruction). The findings underscore the importance of integrating spiritual, philosophical, and practical dimensions in environmental stewardship.